2006
DOI: 10.5751/ace-00105-010306
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Scaup Population Dynamics: What Can Be Learned from Available Data?

Abstract: populations était aussi très sensible aux variations unitaires ou proportionnelles du succès d'éclosion moyen et des taux de survie des canetons ou des juvéniles. Étant donné les faibles effectifs d'échantillons disponibles pour certains aspects-clé du cycle de vie du Petit Fuligule, nous recommandons que des travaux additionnels soient effectués sur les taux vitaux qui ont une influence majeure sur l'accroissement des populations et leur effectif (ex. taux de survie des adultes). Nos modèles de cycle de vie d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 36 publications
(69 reference statements)
6
47
0
1
Order By: Relevance
“…Across multiple studies, between 23% and 63% of annual female scaup mortality occurred during the breeding season (Table ), most of which likely occurred during nesting when females are more susceptible to predation (Koons and Rotella , Bond et al ). Thus, these results reinforce the importance of breeding season events on population dynamics in scaup (Koons et al , ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Across multiple studies, between 23% and 63% of annual female scaup mortality occurred during the breeding season (Table ), most of which likely occurred during nesting when females are more susceptible to predation (Koons and Rotella , Bond et al ). Thus, these results reinforce the importance of breeding season events on population dynamics in scaup (Koons et al , ).…”
Section: Discussionsupporting
confidence: 85%
“…Sea duck species like scoters tend to be relatively long lived (Krementz et al ) and adult survival could have a profound effect on population dynamics, as reported for lesser and greater ( A . marila ) scaup (Flint et al , Koons et al ) and some sea duck species (Mallory ). Thus, filling gaps for these species about sources of variation in adult female survival will provide information about the components that may be controlled by management.…”
Section: Global Climate Indices Anticipated Ecological Effects In Wimentioning
confidence: 99%
“…Our current population models, based on limited data for Boreal-breeding birds, suggest that scaup population dynamics are highly responsive to changes in adult female non-breeding (and breeding) season survival and to a lesser extent on variation in nest and duckling survival rates [40]. If low productivity is more prevalent now than it was historically, it will be important to know whether proposed hunting restrictions for scaup will increase adult and juvenile survival rates to levels that offset this lower production.…”
Section: Discussionmentioning
confidence: 97%
“…Population models based on meta-analyses are useful learning tools, but they confound spatial and temporal variation, which limits guidance for management actions that are directed at specific populations (Morris and Doak 2002, Koons et al 2006, Taylor et al 2012. Here, we used data from one of the longest continuous studies of sage-grouse demography to evaluate both retrospective and prospective vital-rate contributions to the dynamics of a population to determine the most important vital rates for conservation efforts (Caswell 2000, Dobson andOli 2001), and to assess whether current trends in management of this candidate species may need to be reevaluated.…”
Section: Introductionmentioning
confidence: 99%